Réponses

2014-04-27T19:17:09+02:00
X+2y -3z = -4
donc = x = -2y +3z -4

2x +3y +z =11
2 ( -2y +3z -4)
-4y +6z -8 = 11
-4y +6z = 11+8
-4y +6z =20
-4y = -6z +20
y = 6/4z +20/4
y = 3/2z +5

-x-3y+2z = -1
2z = x +3y -1
z = 1/2x +3/2y -12

on sait que x = -2y +3z -4
donc x = -2 (3/2z +5) +3z -4
x = -3z +3z -4
x = -4

z = 1/2x +3/2y -12
z = 1/2*4 +3/2 (3/2z+5) -12
z = 2 +9/4 z +15/2 -12
z -9/4 z = 15/2 -10
4/4z -9/4z = 15/2 -20/2
-5/4z = -5/2
z = -5/2 * -4/5
z =20/10
z =2


y = 3/2z +5
y = 3/2*2 +5
y = 3+5
y = 8